Analysis of patients admitted to the intensive care unit from the emergency department (Annals of Medical Research, 2024)
Aim: To analyze the effects of these data on mortality by examining the demographic data, laboratory findings, most common reasons for hospitalization, duration of hospitalization according to diagnosis and clinics of patients admitted to intensive care units from the emergency department.Materials and Methods: This study was a retrospective analysis of patients hospitalized in the intensive care unit of a secondary care hospital between 01.01.2022 and 31.12.2022. Demographic data, comorbid diseases, laboratory data, diagnosis and length of hospitalization were determined. In-hospital mortality rates were determined and comparative analyses of demographic data and mortality were performed according to diagnoses.Results: The study included 1245 patients. The mean age of the patients was 69.23±15.97 years and 59.9% were male. The most common comorbidities were hypertension (43.5%), diabetes mellitus (23.9%) and coronary artery disease (21%). Cardiology (46.6%), pulmonology (16.3%) and internal medicine (15.7%) were the clinics that admitted the most patients, respectively. The most common diagnoses were acute coronary syndrome (45.7%), pneumonia (22.6%) and acute renal failure (8%). The mean duration of hospitalization was 11.76±7.80 days. The duration of hospitalization was significantly higher in patients with exitus and was 14.93±12.25 days (p=0.000). While 52.4% of the patients were discharged, in-hospital mortality rate was 47.6%. 65.7% of the patients were over 65 years of age and the highest rate of hospitalization was 41.8% in patients over 75 years of age. Although there was a significant difference between the diagnosis and the duration of hospitalization (p=0.000).Conclusion: Comparison of the data between discharged and in-hospital exitus patients in patients admitted to the intensive care unit from the emergency department showed mostly significant differences. Predicting the mortality of these patients, determining the severity of the disease and determining the factors affecting the length of hospitalization are important for the development of new treatment protocols.
Keywords: Emergency department; Intensive care unit; Mortality; Comorbid disease